2008
DOI: 10.1002/mrc.2209
|View full text |Cite
|
Sign up to set email alerts
|

A review with comprehensive data on experimental indirect scalar NMR spin–spin coupling constants across hydrogen bonds

Abstract: Scalar NMR spin-spin coupling constants across hydrogen bonds are fundamental in structural studies and as test grounds for theoretical calculations. Since they are scattered among many articles of different kinds, it seems useful to collect them in the most comprehensive way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
83
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 119 publications
1
83
0
Order By: Relevance
“…As can be observed in Table 2, 4 J FH is around À4.5 Hz for the cis isomers, whereas it is notably smaller, in absolute value, for trans isomers, suggesting that these couplings are mainly transmitted TS as it is already related in literature [3,4] instead of being transmitted through bond.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…As can be observed in Table 2, 4 J FH is around À4.5 Hz for the cis isomers, whereas it is notably smaller, in absolute value, for trans isomers, suggesting that these couplings are mainly transmitted TS as it is already related in literature [3,4] instead of being transmitted through bond.…”
Section: Resultsmentioning
confidence: 75%
“…[1,2] Recently, Alkorta et al [3] published a review reporting nh J X,Y SSCCs including 1h J FH = À 4.42 Hz in 4-bromo-2-fluorophenol. [4] However, there is some evidence that, at least in some instances, O-H. .…”
Section: Introductionmentioning
confidence: 98%
“…We consider this interpretation unwarranted' [note that never did Rae et al [6] suggested that the intramolecular hydrogen bond (IMHB) was strong]. The second aspect is related to a series of papers by Limbach et al [8,10] concerning the 2h J(F-H· · ·N) couplings (about −97 Hz), which are complementary to those studied here. Note that when the proton is transferred, in the first case a very unstable situation Table 1.…”
Section: Introductionmentioning
confidence: 76%
“…[1,2] Later on, some of us published 'A review with comprehensive data on experimental indirect scalar NMR spin-spin coupling constants across hydrogen bonds' [8] where again [6] was cited but not. [1,2] Two other things are relevant in this context.…”
Section: Introductionmentioning
confidence: 99%
“…The tautomeric and exchange processes complicate reliable measurement of the 1 J(N,H) values in many molecules with the hydrogen bonding. [3] Nevertheless, the decrease in the absolute size of the 1 J(N,H) coupling constant by 2-4 Hz in the Z-isomer of 2-(2-acylethenyl)pyrroles (Scheme 1) due to a strong N-H· · ·O intramolecular hydrogen bond was revealed, and this experimental finding was supported by density functional theory (DFT) calculations. [4] However, the increase of the 1 J(N,H) coupling constant by 2-3 Hz was observed in the series of 2-substituted pyrroles with the weak N-H· · ·N(O) intramolecular hydrogen bonds.…”
Section: Introductionmentioning
confidence: 87%